Modeling, forecasting and resource allocation in cognitive radio networks - Akter, Lutfa (Kansas State University, 2010)
With the explosive growth of wireless systems and services, bandwidth has become a treasured commodity. Traditionally, licensed frequency bands were exclusively reserved for use by the primary license holders (primary users), whereas, unlicensed frequency bands allow spectrum sharing. Recent spectrum measurements indicate that many licensed bands remain relatively unused for most of the time. Therefore, allowing secondary users (users without a license to operate in the band) to operate with minimal or no interference to primary users is one way of sharing spectrum to increase efficiency. Recently, Federal Communications Commission (FCC) has opened up licensed bands for opportunistic use by secondary users. A cognitive radio (CR) is one enabling technology for systems supporting opportunistic use. A cognitive radio adapts to the environment it operates in by sensing the spectrum and quickly decides on appropriate frequency bands and transmission parameters to use in order to achieve certain performance goals. A cognitive radio network (CRN) refers to a network of cognitive radios/secondary users. In this dissertation, we consider a competitive CRN with multiple channels available for opportunistic use by multiple secondary users. We also assume that multiple secondary users may coexist in a channel and each secondary user (SU) can use multiple channels to satisfy their rate requirements. In this context, firstly, we introduce an integrated modeling and forecasting tool that provides an upper bound estimate of the number of secondary users that may be demanding access to each of the channels at the next instant. Assuming a continuous time Markov chain model for both primary and secondary users activities, we propose a Kalman filter based approach for estimating the number of primary and secondary users. These estimates are in turn used to predict the number of primary and secondary users in a future time instant. We extend the modeling and forecasting framework to the case when SU traffic is governed by Erlangian process. Secondly, assuming that scheduling is complete and SUs have identified the channels to use, we propose two quality of service (QoS) constrained resource allocation frameworks. Our measures for QoS include signal to interference plus noise ratio (SINR) /bit error rate (BER) and total rate requirement. In the first framework, we determine the minimum transmit power that SUs should employ in order to maintain a certain SINR and use that result to calculate the optimal rate allocation strategy across channels. The rate allocation problem is formulated as a maximum flow problem in graph theory. We also propose a simple heuristic to determine the rate allocation. In the second framework, both transmit power and rate per channel are simultaneously optimized with the help of a bi-objective optimization problem formulation. Unlike prior efforts, we transform the BER requirement constraint into a convex constraint in order to guarantee optimality of resulting solutions. Thirdly, we borrow ideas from social behavioral models such as Homo Egualis (HE), Homo Parochius (HP) and Homo Reciprocan (HR) models and apply it to the resource management solutions to maintain fairness among SUs in a competitive CRN setting. Finally, we develop distributed user-based approaches based on ``Dual Decomposition Theory" and ``Game Theory" to solve the proposed resource allocation frameworks. In summary, our body of work represents significant ground breaking advances in the analysis of competitive CRNs.
Keywords: Cognitive radio; Power; Rate; Distributed; Fairness; Game theory; Engineering, Electronics and Electrical (0544)